Ordinary matter - Elvery, Laura (UQP, University of Queensland Press, 2020)
You run towards love – Grand Canyon – Something close to gold – Night blindness – Hyperobject – Frost – Stockholm – Corn queen – Growth – Witnessing – Fruit flies – Titan Arum – The bodies are buried – Better nature – Wingspan – The garden bridge – The town turns over – Little fly – The fix – A brief history of petroleum. In 1895 Alfred Nobel rewrote his will and left his fortune made in dynamite and munitions to generations of thinkers. Since 1901 women have been honoured with Nobel Prizes for their scientific research twenty times, including Marie Curie twice. Spanning more than a century and ranging across the world, this inventive story collection is inspired by these women whose work has altered history and saved millions of lives. From a transformative visit to the Grand Canyon to a baby washing up on a Queensland beach, a climate protest during a Paris heatwave to Stockholm on the eve of the 1977 Nobel Prize ceremony, these stories interrogate the nature of inspiration and discovery, motherhood and sacrifice, illness and legacy. Sometimes the extraordinary pivots on the ordinary
Keywords: Women Nobel Prize winners; Women in science; Australian fiction; Fiction; History; Short stories